Tissue content of sulfomucins and sialomucins in the colonic mucosa, without fecal stream, undergoing daily intervention with sucralfate - Bonassa,Christiny Emmanuelle Gabriel (2015)
PURPOSE: To measure the content of acidic mucin, sialomucin, and sulfomucins in the colonic mucosa without fecal stream submit to intervention with sucralfate (SCF).METHODS: Thirty-six rats were submitted to a right colostomy and a distal mucous fistula and divided into two groups according to sacrifice to be performed two or four weeks. Each group was divided into three subgroups according daily application of enemas containing saline, SCF at 1.0 g/kg/day or 2.0 g/kg/day. Colitis was diagnosed by histological analysis. Acid mucins were determined with the Alcian-Blue and sulfomucin and sialomucin by high iron diamine-alcian blue (HID-AB) techniques. The mucins were quantified by computer-assisted image analysis. Mann-Whitney and ANOVA tests were used to analyze the results establishing the level of significance of 5% for both (p<0.05).RESULTS: SCF enemas decreased the inflammation score and was related to the concentration used and time of the intervention. SCF at both concentrations increased the content of acid mucin, which was related to the concentration used and to the improvement in the inflammatory score. There was an increase in the content of sulfomucins and sialomucins in SCF groups. SCF increased sulfomucins from 2 weeks of intervention, which was not related to the dose or time of application. The increase in sialomucin content was related to the time and dose used in the intervention.CONCLUSION: Sucralfate increased the content of acidic mucins, primarily at the expense of sialomucin, which was affected by the dose and time of intervention.